Stereoselective synthesis of pentasubstituted 1,3-dienes via Ni-catalyzed reductive coupling of unsymmetrical internal alkynes - Zhou, Zhijun (Chem Sci, 2020)
The reductive coupling of alkynes represents a powerful strategy for the rapid synthesis of highly substituted 1,3-dienes. This method has the advantages of high atom and step economy, and readily available substrates. Unfortunately, the intermolecular coupling of unsymmetrical internal alkynes remains extremely challenging due to the difficulty in controlling self-dimerization and cross-coupling, as well as stereo- and regioselectivity. Previous reports are still limited to intramolecular processes or the use of stoichiometric amounts of metal catalyst. Herein, we report that nickel-catalyzed reductive coupling of two unsymmetrical internal alkynes can overcome the above-mentioned limitations by using a hemilabile directing group strategy to control the regioselectivity. A series of synthetically challenging penta-substituted 1,3-dienes are obtained in good yields with high regio- and enantioselectivity (mostly > 20/1 rr, >90% ee).